ASSESSMENT OF PRAKRITI IN DIFFERENT DESHA - Rohra priya; Meena.M.S (International Journal of Applied Ayurved Research, 2015)
Prakriti is a nature; it is different in every individual. It depends upon the dosha which are predominant at the time of conception (sukra-shonit sanyog). Some other factors like- jati, kula, desh, kala, vaya, and pratyatmaniyata also play important role in the formation of prakrit in Janmottar. Among these factors we focused the role of desha in the formation of prakriti. Desh is three types, Sadharana, Jangal & Aanoop. Tridoshaja, Vata-Pitta & Kapha–Vata has predominance in Sadharana, Jangal & Aanoop desh respectively. Total 90 individual were selected, 30 from each desh. In this study we found Pitta Pradhan prakriti in Sadharana desha, Vata Pradhan Prakriti in Jangal desha & Kapha Pradhan Prakriti in Aanoop desha.